Does groundwater protection in Europe require new EU-wide environmental quality standards? - Balderacchi, Matteo; Filippini, Maria; Gemitzi, Alexandra; Klöve, Björn; Petitta, Marco; Trevisan, Marco; Wachniew, Przemysław; Witczak, Stanisław; Gargini, Alessandro (Frontiers in Chemistry, 2014)
The European Groundwater Directive could be improved by limiting the scopes of the Annexes I and II to the manmade and natural substances, respectively, and by defining a common monitoring protocol. The changes in the European landuse patterns, in particular the urban sprawl phenomena, obscure the distinction between the point and diffuse sources of contamination. In the future more importance will be given to the household contamination. Moreover, the agricultural environment could be used for developing new conceptual models related to the pharmaceuticals.